A multicentric survey on antimicrobial use and hospital acquired infections among patients admitted in tertiary care centers in India - Prof Nusrat Shafiq; Dr. Samiksha Bhattacharjee; Dr. Ashish Kumar Kakkar; Mr. Chakrant Mothsara; Dr. Prasan Kumar Panda; Dr. Naveen Murali (International Journal of Infectious Diseases)
Background: Amid global apprehensions about the escalating threat of antimicrobial resistance (AMR), the significance of Point Prevalence Surveys (PPS) in comprehending antibiotic consumption and resistance cannot be overstated. This multicentre survey was planned and conducted to quantify antibiotic use, indications, identify organism isolates amongst other data for planning and strengthening antimicrobial stewardship programmes across India. Methods: Conducted over two weeks, this cross-sectional study employed a staggered approach among eight tertiary care hospitals spread across India. Encompassing acute, chronic care, and intensive care units, digital data collection utilized pre-designed patient, ward, and HAI forms. The study used custom digital tools for antibiotic assessments, with site training. Inclusions: hospitalized patients on systemic antimicrobials. Exclusions: outpatient/day-care, dialysis patients, those receiving topical antimicrobials, or in emergency/observation wards. Assessment of rationality of prescriptions was additionally carried out in a subset of prescriptions Results: Data from 3968 patients across eight tertiary care hospitals in India revealed notable patterns. Analysis found that out of 6575 total beds, 1887 (28.69%) had ventilatory care facilities. Out of 4248 antibiotic prescriptions, the top five antibiotics prescribed were ceftriaxone (632), metronidazole (435), Amikacin (370), Piperacillin, and tazobactam (369), and Meropenem (301), of them 47.5% were from WHO Access group, 42.16% from Watch group and 5.08% from Reserve group. Community-acquired infection and surgical prophylaxis emerged as major indications for which antibiotics were prescribed (1183,793 cases respectively). Differences were noted in the patterns for pediatric and adult populations as well as newly formed institutes versus those which are more than a decade old. Empiric antibiotic prescriptions were most common overall (2080 prescriptions), but some sites showed prophylactic therapy as the primary reason of antibiotic use. Double-anaerobic coverage and extended duration of surgical prophylaxis was found to be most common redundant cover prescribed by clinicians. Conclusion: While the survey allows evaluation of changes for the centers who had previously participated while it generated baseline information in the centers who were not previously initiated. The findings lay the foundation for ongoing and focused Antimicrobial Stewardship Interventions and underscore the imperative for targeted surveillance and strategic antibiotic stewardship initiatives.